An Analysis of Persuasive Techniques Used in Maybelline New York's Instagram Captions - Sylva Auliya; Sri Hastuti (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2022)
This study, entitled “An Analysis of Persuasive Techniques Used in Maybelline New York’s Instagram Captions” is about analyzing the persuasive techniques found in the Instagram caption of Maybelline New York. The aims are to find the persuasive techniques, the most persuasive techniques, and the meanings of the persuasive sentences used in Maybelline New York’s Instagram captions. Lamb and Bonacci’s theories are used in this study, and qualitative method is also applied in this study. This study found 11 persuasive techniques out of 33 techniques of Lamb’s theory used by Maybelline New York. They are Everyday/Colloquial Language, Emotive Language, Rhetorical Question, Hyperbole, Connotation, Imagery, Metaphor, Simile, Repetition, Assonance, and Analogy. The most used persuasive techniques are Everyday/colloquial language (16.12%), rhetorical questions (7.74%), hyperbole, and connotation have the same percentage (7.09%). Relating to the meaning, the use of everyday/colloquial language is to help conveys the point to readers. Rhetorical question is used to lead readers to understand the message. Hyperbole is used to raise readers’ interest, and connotation is used to help tell something differently.